Aspecto: núcleo licenciador da alternância incoativa no PB - Maria Jose de Oliveira (2011)
This dissertation aims to investigate the causative-inchoative construction in Brazilian Portuguese. In order to establish which arguments are selected by these verbs as well as to understand how the aspectual features [+inchoative] and [+telic] are encoded, the verbs were grouped into two sets. In the first set, I include verbs like apodrecer (to rot), which visibly carry the inchoative morpheme {-ec-}. On the other hand, in the second set, I grouped verbs like quebrar (to break), which do not exhibit visible inchoative morphology. The investigation starts from Hale & Keyser's (1993; 2002) observation that the argument structure of such verbs must possess a semantic component called manner, which allows them to alternate. On the other hand, when this semantic component is not present within the lexical VP, the inchoative alternation is then blocked. Based on these intuitions, the hypothesis assumed isthat the semantic component manner corresponds to the aspectual feature [+inchoative]. Consequently, I hypothesize that this feature must be coindexed with the internal argument in [Spec-VP]. Therefore, it is the presence of this feature on the predicate meaning that is directly responsible for us to obtain the change of state interpretation of the internal argument. The result of such analysis is that we will have to assume that predicates expressing punctual change must exhibit a [+telic] reading.